PENGARUH PENERAPAN TEORI GESTALT TERHADAP PENINGKATAN KEMAMPUAN PEMAHAMAN MASALAH SOSIAL PESERTA DIDIK PADA PEMBELAJARAN IPS DI SMPN 24 SURABAYA - Fitrah Yasmin (Jurnal Dialektika Pendidikan IPS, 2026)
This study aims to analyze the effect of applying Gestalt Theory on improving students' ability to understand socialissues in social studies classes at SMP Negeri 24 Surabaya. The study employed a quantitative approach using aquasi-experimental design involving an experimental class and a control class, each consisting of 28 students. Datawere collected through multiple-choice tests (pretest and posttest), questionnaires, and documentation that had beentested for validity and reliability. Data analysis used prerequisite tests (normality and homogeneity) and a nonparametric hypothesis test (Mann-Whitney U Test), supplemented by an N-Gain test to measure treatmenteffectiveness. The results indicate that the application of Gestalt Theory is significantly more effective in enhancingstudents' understanding of social issues compared to conventional learning. This is evidenced by the Mann-Whitneysignificance value of 0.000 < 0.05 and the experimental group's N-Gain of 83%, classified as effective, while thecontrol group obtained only 13.96%, classified as ineffective. All students in the experimental class (100%) reachedthe high category in the posttest. The application of four Gestalt principles (Pragnanz, Similarity, Closure, andFigure-Ground) was proven to create meaningful, contextual, and participative learning, significantly contributing tobuilding comprehensive and integrated understanding of social issues.